An evaluative case study of the YiPSA prison post-release programme in Cape Town, South Africa - Osbourn, Clinton (Department of Social Development, 2023)
This research study explored the perceptions of a group of young men that participated in a prison post-release programme implemented by Young in Prison South Africa (YiPSA) based in Cape Town, South Africa, that used primarily arts-based methods to engage the participants. It aimed to explore their perceptions of whether or not participating in the programme affected their attitudes and behaviour, with a particular focus on factors that are associated with desistance. It also aimed to explore which aspects of the programme they considered to be the most significant in affecting their attitudes and behaviours. The research was conducted using an evaluative case study approach. In-depth interviews were conducted with 12 respondents that had participated in the programme between 2013 and 2015, in order to gain an understanding of their perceptions about how their behaviour had changed and what aspects of the programme they thought were most influential in bringing about these changes. The research found that nearly all the respondents reported that their behaviour had shifted to become more empathetic, and their life skills had improved, most particularly their communication skills. They also reported a decrease in criminal activity and changes in their aspirations to more prosocial ambitions as well as improved self-esteem and a newfound purpose. They also reported that they had experienced a shift in their identities, which many scholars believe is necessary for desistance to be maintained. They attributed these changes to a combination of various factors. This included the sense of belonging that they felt while participating in the programme, which was nurtured by the supportive relationships with staff and the non-judgemental environment. They also referred to learning new skills and exposure to new experiences, which were linked to the creative projects that they completed while attending the programme. The findings of the research indicate that the creative methods that were utilized were an effective way of engaging the young people when they left prison, as they appealed to their interests and gave them opportunities to learn new skills as well as practice behaviours that are associated with desistance. Recommendations are made for the Department of Correctional Service as well as nongovernmental organisations and social service professionals who are working with this target group.